Forecasting the land use change of urban coastal area in Banda Aceh and its impact on urban sustainability using LandUseSIM cellular automata simulation model. - Issana Meria Burhan; Ashfa Achmad; Putra Rizkiya; Zainuddin Hasan (Graduate Program of Syiah Kuala University, 2020)
The dynamics of urban development, followed by various opportunities and challenges for different social groups, indicate a growing sense of complexity, unpredictability, and insecurity about cities and emphasis a need to identify new sustainability strategies. This paper aims at predicting the land-use change of urban coastal areas in Banda Aceh and its impact on urban sustainability. It used an urban simulation model using Cellular Automata (CA), integrated into a LanduseSIM platform. There were three main steps as part of the research methodology: (1) preparation of current data on land uses (2015), (2) simulation of data using CA in LanduseSIM software, and (3) visualization of data and result. Accordingly, the final simulation of the year 2030 was completed, in two scenarios, as the basis to evaluate the impact of land-use change on urban sustainability in Banda Aceh. The study has revealed that the current development trend in the coastal area of Banda Aceh is consuming natural resources such as wetlands and vegetation, driven particularly by the planning of urban coastal region as a center of tourism and fishery, complemented by the upcoming Banda Aceh Outer-Ring Road project. The study recommends a reconsideration of the city strategies by decision-makers to achieve sustainability and ensure ecological balance.